Positional match demands of professional rugby league competition - Sirotic, A. C.; Knowles, H.; Catterick, C.; Coutts, A. J. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine the differences in physical performance and game-specific skill demands between 5 positional groups in a professional rugby league team. Positional groups consisted of the backs (n = 8), forwards (n = 8), fullback (n = 7), hooker (n = 8), and service players (n = 8). Time-motion analysis was used to determine physical performance measures (exercise intensity, distance travelled, time, frequency, and speed measures) and game-specific skill measures (ball carries, supports, ball touches, play the balls, and tackling indices) per minute of playing time. The main finding was that the fullback completed more very high-intensity running (VHIR) because of more support runs when compared to all other positional groups (p = 0.017). THe VHIR (p = 0.004) and sprinting indices (p < 0.002) were also greater in the second half of a match for the fullback than in any other positional group. The hooker spent more time jogging than the backs and forwards (p < 0.001) and touched the ball on more occasions than any other positional group (p < 0.001). The backs spent more time walking than the forwards, hooker, and service players (p < 0.001). The forwards, hooker, and service players completed more tackles per minute during a match than the backs and fullback (p < 0.001). The fullback and forwards also ran the ball on more occasions than the backs, hooker, and service players did (p < 0.001). These results show that positional roles play an important part in determining the amount of physical and game-specific skill involvement during match play.